Factores de riesgo de las hemorragias digestivas en pacientes adultos y su relación con la anemia crónica que acuden al Hospital el Corazón, del cantón Pangua, durante el segundo semestre del 2014 - Azas Tigselema, Sara Yolanda (2015)
Gastrointestinal bleeding is referred to as blood loss in any segment of the digestive tract from the esophagus to the anus, can be high or low, the causes may be anatomical, vascular, inflammatory, neoplastic also is related to the incidence of factors risks such as alcoholism, peptic ulcer, diabetes mellitus, hypertension, haematemesis, gastric ulcer, erosive gastritis, heart insufiencia, renal insufieciencia. The performance of nursing for patients with gastrointestinal bleeding is part of the health policy of our country is in line with international regulations on the achievement of increased life expectancy, the use of technology and the protection of human integrity, among others, elements that are essential to achieve a high level of health of our population. According to the World Health Organization (WHO) reports that it could annually up to 50% of gastrointestinal events and mortality has not changed over the years remained between 8 and 10% despite advances in drug therapy, endoscopic intervention and intensive care management. In Ecuador it is estimated that ranges from 21 to 28% having gastrointestinal bleeding, acute gastric mucosal lesions, peptic ulcer, duodenal ulcer influenced by factors chronic consumption of alcoholic beverages, smoking, liver disease, hematemesis, chronic anemia. This study was conducted in the heart of the Canton Hospital Pangua adult patients where the number is growing rapidly, having as our overall objective is to identify risk factors for gastrointestinal bleeding and its relation to chronic anemia.Keywords: gastrointestinal bleeding, gastric mucosa, peptic ulcer, duadenal, gastric ulcer, heart failure, renal failure KEYWORDS: risk factors, gastrointestinal bleeding, anemia, gastrointestinal bleeding symptoms, causes and consequences of gastrointestinal bleeding, hematemesis